2017
DOI: 10.1038/srep45690
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Subcellular Proteomics Analysis of Susceptible and Near-isogenic Resistant Bombyx mori (Lepidoptera) Larval Midgut Response to BmNPV infection

Abstract: The molecular mechanism of silkworm resistance to Bombyx mori nucleopolyhedrovirus (BmNPV) infection remains largely unclear. Accumulating evidence suggests that subcellular fractionation combined with proteomics is an ideal technique to analyse host antiviral mechanisms. To clarify the anti-BmNPV mechanism of the silkworm, the near-isogenic line BC9 (resistant strain) and the recurrent parent P50 (susceptible strain) were used in a comparative subcellular proteomics study. Two-dimensional gel electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…With the use of recently emerging data, researchers have begun to uncover the antiviral mechanisms in invertebrate immunity, particularly by screening for antiviral genes (Xia et al ., ; Bao et al ., ; Zhou et al ., ; Lekha et al ., ; Wang et al ., ; ; ; Xu et al ., ; Li et al ., ; Yu et al ., ). Whether these genes are resistance‐related genes remains unclear, however, and the exact antiviral mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of recently emerging data, researchers have begun to uncover the antiviral mechanisms in invertebrate immunity, particularly by screening for antiviral genes (Xia et al ., ; Bao et al ., ; Zhou et al ., ; Lekha et al ., ; Wang et al ., ; ; ; Xu et al ., ; Li et al ., ; Yu et al ., ). Whether these genes are resistance‐related genes remains unclear, however, and the exact antiviral mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative subcellular proteomics study on the susceptible strain, P50 and the derived resistant near‐isogenic strain BC9 showed that 16 proteins were potentially involved in repressing BmNPV infection (Wang et al ., ). Comparative genomics, transcriptomics and proteomics analyses also revealed that numerous genes and proteins are possibly involved in resistance against BmNPV (Bao et al ., , , ; Zhou et al ., ; Wang et al ., , ; Li et al ., ; Yu et al ., ). Among these, V‐ATPase and Bm‐SP142 are upregulated in resistant strains (Lü et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Two-dimensional electrophoresis and mass spectrometry (MS) techniques, isobaric tags for relative and absolute quantification (iTRAQ), Tandem Mass Tags (TMT) and label-free methods are attractive proteomic analysis technologies for researching the interaction between pathogens and B. mori. Wang et al [12] performed a comparative subcellular proteomics analysis of the silkworm larval midgut response to BmNPV infection by 2-DE combined with MS. The iTRAQ method was also used to explore the molecular mechanisms of B. mori response to B. mori cypovirus (BmCPV) [13] and BmNPV [14] challenge.…”
mentioning
confidence: 99%
“…Furthermore, a GP64binding protein E3 ubiquitin-protein ligase SINA-like 10 (SINAL10) [20] and chaperonin containing t-complex polypeptide 1 (TCP-1) [21] could stimulate BmNPV proliferation in BmN cells. Some studies regarding the role of the B. mori larval midgut in response to BmNPV infection have been conducted in previous studies utilizing RNA-Seq [22], 2-DE combined MS [12], label free [16] and iTRAQ methods [14]. Hu et al [6] investigated changes in the protein composition of the silkworm digestive juice between non-infected and infected samples by shotgun and MS techniques.…”
mentioning
confidence: 99%
“…It is also a lepidopteran model organism for genetic and immunology research (Liu, Ling, & Wu, 2009;Rao et al, 2016;Wang et al, 2017). In silkworms, the Rab protein mainly functions in the development of neurons (Uno et al, 2010(Uno et al, , 2013(Uno et al, , 2014(Uno et al, , 2016(Uno et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%